Successful Integration of Membrane Technologies in a Conventional Purification Process of Tannery Wastewater Streams - Angelo Chianese; Diana Sannino; Olga Sacco; Marco Stoller (Membranes, 2013)
The aim of this work is to design and integrate an optimized batch membrane process in a conventional purification process used for the treatment of tannery wastewater. The integration was performed by using two spiral wound membrane modules in series, that is, nanofiltration and reverse osmosis, as substitutes to the biological reactor. The membrane process was designed in terms of sensible fouling issues reduction, which may be observed on the nanofiltration membrane if no optimization is performed. The entity of the fouling phenomena was estimated by pressure cycling measurements, determining both the critical and the threshold flux on the nanofiltration membrane. The obtained results were used to estimate the need of the overdesign of the membrane plant, as well as to define optimized operating conditions in order to handle fouling issues correctly for a long period of time. Finally, the developed membrane process was compared, from a technical and economic point of view, with the conventional biological process, widely offered as an external service near tannery production sites, and, here, proposed to be substituted by membrane technologies.